Pendekatan Diagnostik Terhadap Leukemia Akut - Vinson Hartoyo; Andree Kurniawan (Medicinus, 2018)
Acute leukemia is the most common form of cancer in children, comprises approximately 30 percents of all childhood malignancies, with acute lymphoblastic leukemia (ALL) being five times more common than acute myeloid leukemia (AML)1. Despite the advance in the treatment of acute lymphobalstic leukemia, five-year event free survival rate still remain quite low in group of patient with advanced age of onset (40% or below in later age)2,3,4. A case of 17 year old girl presented with 3 day onset of profuse bleeding from her nostril, ear, gums and gastrointestinal tract (melena and hematemesis). Blood count and peripheral blood smear revealed a pancytopenia with 26% blast count lymphocyte dominant, and reticulocyte percentage of 0.26% which is signalling a bone marrow failure. The patient was planned to undergo a bone marrow transplant before finally died on third day of care.